Respiratory Infections - Pokorski, Mieczyslaw (Advances in Experimental Medicine and Biology,, 2015)
The successful prophylaxis and treatment of ubiquitous respiratory infections is essential for the enhancement of public health. The chapters provide new insights into the biology of causative pathogens, tackle the epidemiological aspects, and present an update on diagnostics, prevention and therapy of infections. The emerging new pathogens and antibiotic resistance of the old ones are discussed. Novel markers of the severity of community acquired pneumonia, which bears high morbidity and mortality, also are presented.